Análisis comparativo del perfil de resistencia antimicrobiana de listeria spp. en muestras de leche cruda. - Pinto Cayambe, Alex Patricio (2025)
Raw milk is a food with high nutritional value; however, its consumption without adequate thermal treatment poses a public health risk, especially in contexts with limited hygiene practices. Listeria spp. is an emerging pathogen associated with foodborne diseases (FBDs), characterized by a high mortality rate and increasing antimicrobial resistance. This study aimed to analyze the antimicrobial resistance profile of Listeria spp. isolated from raw milk samples sold in three markets in the Guaranda canton, Bolívar province. The research was based on the microbiological identification of the bacterium and the evaluation of its susceptibility to three commonly used antibiotics: ampicillin, ciprofloxacin, and tetracycline. A completely randomized block design (CRBD) was applied, including biochemical, microscopic, and disk diffusion (Kirby-Bauer) tests. The results revealed a prevalence of 66.67% of Listeria spp. in the analyzed samples. Susceptibility testing showed total resistance to ampicillin and tetracycline, while ciprofloxacin exhibited significant inhibitory activity. The statistical analysis (ANOVA) indicated highly significant differences between treatments (p < 0.0001), leading to the rejection of the null hypothesis and confirming significant variation in resistance profiles. These findings highlight the presence of multidrug-resistant strains in dairy products lacking sanitary control, posing a latent risk to consumers. In conclusion, the study underscores the urgent need to strengthen microbiological surveillance, regulate antibiotic use in animal production, and promote the consumption of pasteurized milk. Further studies on bacterial resistance and the implementation of comprehensive sanitary measures in the rural dairy sector are recommended.